PANEL STUDY OF CREDIT MANAGEMENT DIMENSIONS AND LOAN PERFORMANCE OF NIGERIAN BANKS - Oloruntoba Oyedele; A. O Ahmed (Malete Journal of Accounting and Finance, 2023)
The study examines the impact of credit management dimensions on loan performance of Nigerian banks. The study adopted a quantitative approach that employed the ex-post facto research design that focused on the panel data study. The population consisted of the entire 22 listed banks in Nigeria according to the report made by CBN (2019). The sample size is made up of 10 listed banks that are listed before the year 2010 and were not delisted before the year 2019. This was used to provide an adequate time frame necessary to establish the causes and effect of the occurrence. The methods of analysis were correlation and regression. The study establishes that credit risk has a positive relationship with the loan performance of Nigerian banks while interest spread and interest rate charged have a negative relationship with the loan performance of Nigerian banks. This implies that the interest rate charged and increase in interest disparity employed by Nigerian banks has led to poor loan performance. The study, therefore, recommends that Nigerian banks should apply efficient and effective credit risk management that will ensure that loans are matched with ability to repay, loan defaults are projected accordingly, and relevant measures taken to minimise the same. Nigerian banks should also enhance periodic credit risk monitoring of their loan portfolio to increase the loan performance